Can carbon capture and storage unlock `unburnable carbon'? - Budinis,S; Mac,Dowell N; Krevor,S; Dixon,T; Kemper,J; Hawkes,A (Elsevier Science BV, 2017)
The concept of ‘unburnable carbon’ emerged in 2011, and stems from the observation that if all known fossil fuel reserves are extracted and converted to CO2(unabated), it would exceed the carbon budget and have a very significant effect on the climate. Therefore, if global warming is to be limited to the COP21 target, some of the known fossil fuel reserves should remain unburnt. Several recent reports have highlighted the scale of the challenge, drawing on scenarios of climate change mitigation and their implications for the projected consumption of fossil fuels. Carbon Capture and Storage (CCS) is a critical and available mitigation opportunity and its contributionto timely and cost-effective decarbonisation of the energy system is widely recognised. However, while some studies have considered the role of CCS in enabling access to more fossil fuels, no detailed analysis on this issue has been undertaken. This paper presents a critical review focusing on the technologies that can be applied to enable access to, or ‘unlock’, fossil fuel reserves in a way that will meet climate targets and mitigate climate change. It also quantifies the impact of CCS in unlocking unburnable carbon in the first and in the second half of the century.